STORYTELLING UNTUK MENGATASI PERILAKU AGRESIF ANAK - Solichah, Novia (Universitas Islam Negeri Imam Bonjol Padang, 2020)
This research aims to know the influence of storytelling to overcome the aggressive behavior of child. This experimental quantitative study uses single case experiment design. Data collection is conducted through a series of assessment such as observation, interviews, graphic tests (HTP, DAP, BAUM) and CBCL. After the intervention, the subject shows a positive change in his behavior. The subject is willing and able to be obedient and polite to the teacher, not screaming, not hitting, kicking, pinching and picking up a friend's seat, calling a friend with a good call or according to name, requesting permission before asking or borrowing a friend's goods, and would apologize if guilty. In other words, storytelling is able to help overcome the aggressive behavior of child.